The labor share of income around the world: Evidence from a panel dataset - Marta Guerriero (Asian Development Bank Institute (ADBI), 2019)
There are two fundamental reasons why factor shares have traditionally been overlooked in the economic literature. First, because of their nature, factor shares are conceptually difficult to define and measure. Second, they have for a long time been perceived as constant across time and space. In this study, we provide an evaluation of five different methodologies of estimation commonly used in the labor share literature and propose a new measurement. We then compile a global dataset of the labor income share across 151 economies - both developing and developed - for all or part of the period 1970-2015. Results show that our suggested indicator is correlated to the other five measures but it also retains unique information. Contrary to the traditional assumption of stable factor shares, we document the existence of considerable heterogeneity across economies and variability over time. Specifically, there has been a general decline in the labor share around the world, in particular from the mid-1980s onwards.
Keywords: E25; J30; E01; 330; factor shares; income distribution; labor